Level of discharge readiness and influencing factors in ischaemic stroke patients: a descriptive, cross-sectional study - Bai, Xiaolu; Gao, Lei; Li, Hongli; Li, Ruiling; Zhang, Ying; Han, Lingyu; Liang, Dandan; Wang, Yining; Zhang, Yurui; Yang, Wenjia (Frontiers in Neurology, 2025)
ObjectivesThis study aims to evaluate readiness for hospital discharge (RHD) levels in ischemic stroke patients and identify influencing factors, providing evidence for targeted post-discharge interventions to improve secondary prevention outcomes.Materials and methodsIn this context, we conducted a descriptive cross-sectional study to investigate and analyse the factors influencing discharge readiness among 220 patients with ischaemic stroke from 1 June to 31 December 2024 in a tertiary hospital in China. Statistical analyses were performed using SPSS 26.0, with significant results visualised in GraphPad Prism 9.0. Descriptive statistical analysis of frequency, component ratio, and mean±standard deviation was conducted using a self-made general sociological data and disease characteristics questionnaire, the Readiness for Hospital Discharge Scale (RHDS), and the Quality of Discharge Teaching Scale (QDTS), and single-factor analysis was performed by independent sample t-test and one-way ANOVA. Pearson correlation analysis was used to describe the relationship between the two scales. Single-factor and correlation analyses of statistically significant variables were included in the equation, and multiple stepwise linear regression analysis was performed to test, interpret, and analyse the collected data.ResultsThe readiness score of ischaemic stroke patients, as measured by the readiness scale, was 6.13 ± 0.75 points. Results from multiple linear regression analysis indicated that the quality of discharge guidance, length of hospital stay, presence of comorbid conditions, frequency of stroke occurrence, and mRS scores were independent factors influencing caregiver readiness (p < 0.05).ConclusionReadiness for discharge among ischaemic stroke patients is inadequate and positively correlated with the quality of discharge guidance. Patients with shorter hospital stays, a higher number of comorbid conditions, increased frequency of stroke occurrence, and higher mRS scores exhibited lower readiness for discharge. These findings suggest that healthcare professionals should enhance the quality of discharge education and provide targeted interventions for patients with shorter hospitalisation and more severe conditions. Additionally, establishing a secondary prevention support mechanism is essential to improve discharge readiness and ensure better post-discharge outcomes for ischaemic stroke patients. This will ensure their safe transition from hospital to home.